Clinical Overview of Arthritis with a Focus on Management Options and Preventive Lifestyle Measures for its Control - Gupta, Umesh C.; Gupta, Subhas Chandra; Gupta, Saira Sugandh (Current Nutrition & Food Science, 2022)
Arthritis is the spectrum of conditions that cause swelling and tenderness of one or more body joints with key symptoms of joint pain and stiffness. Its progression is closely linked to age. Although there are a number of arthritis types, such as ankylosing, gout, joint infections, juvenile idiopathic, reactive, and septic, the two most common types are osteoarthritis and rheumatoid arthritis. Osteoarthritis causes the articulating smooth cartilage that covers the ends of bones, forming a joint, to break down. Rheumatoid arthritis is a disease in which the immune system attacks joints, beginning with the cartilaginous lining of the joints. The latter is considered a systemic disease, i.e., affecting many parts of the body, but the respiratory system is involved in 10 to 20% of all mortality. Osteoarthritis is one of the leading causes of disability globally. Several preventive measures to control arthritis have been suggested, such as using analgesics, non-steroid anti-inflammatory drugs, moderate to vigorous physical activity and exercise, reducing sedentary hours, getting adequate sleep, and maintaining healthy body weight. Foods including a Mediterranean diet rich in fruits and vegetables, fish oil, medicinal plants, and microbiota are vital protective methods. The intake of vitamins, such as A and C, minerals, e.g., selenium and zinc, polyunsaturated and n-3 fatty acids, is also a significant preventive measure.
Keywords: rheumatoid